Treatment and disease progression in a birth cohort of vertically HIV-1 infected children in Ukraine - Pilipenko Tatyana; Semenenko Igor; Malyuta Ruslan; Mahdavi Saboura; Thorne Claire (BMC, 2010)
Abstract Background Ukraine has the highest HIV prevalence (1.6%) and is facing the fastest growing epidemic in Europe. Our objective was to describe the clinical, immunological and virological characteristics, treatment and response in vertically HIV-infected children living in Ukraine and followed from birth. Methods The European Collaborative Study (ECS) is an ongoing cohort study, in which HIV-1 infected pregnant women are enrolled and followed in pregnancy, and their children prospectively followed from birth. ECS enrolment in Ukraine started in 2000 initially with three sites, increasing to seven sites by 2009. Results A total of 245 infected children were included in the cohort by April 2009, with a median age of 23 months at most recent follow-up; 33% (n = 77) had injecting drug using mothers and 85% (n = 209) were infected despite some use of antiretroviral prophylaxis for prevention of mother-to-child transmission. Fifty-five (22%) children had developed AIDS, at a median age of 10 months (IQR = 6-19). The most prevalent AIDS indicator disease was Pneumocystis jiroveci pneumonia (PCP). Twenty-seven (11%) children had died (median age, 6.2 months). Overall, 108 (44%) children had started highly active antiretroviral treatment (HAART), at a median 18 months of age; median HAART duration was 6.6 months to date. No child discontinued HAART and 92% (100/108) remained on their first-line HAART regimen to date. Among children with moderate/severe immunosuppression, 36% had not yet started HAART. Among children on HAART, 71% (69/97) had no evidence of immunosuppression at their most recent visit; the median reduction in HIV RNA was 4.69 log10 copies/mL over a median of 10 months treatment. From survival analysis, an estimated 94%, 84% and 81% of children will be alive and AIDS-free at 6, 12 and 18 months of age, respectively. However, survival increased significantly over time: estimated survival rates to 12 months of age were 87% for children born in 2000/03 versus 96% for those born in 2004/08. Conclusion One in five children had AIDS and one in ten had died. The half of children who received HAART has responded well and survival has significantly improved over time. Earlier diagnosis and prompt initiation of HAART remain key challenges.